2012
DOI: 10.6000/1927-7229.2012.01.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Molecular Therapy in Cerebral Gliomas

Abstract: Despite innovative therapeutic strategies, the expectative of life in patients affected by cerebral gliomas remain dismal. Malignant gliomas represent a class of infiltrative and aggressive neoplasms that are generally resistant to multimodal approach. The efficacy of classical anti-cancer strategies is seriously limited by lack of specific therapies against malignant cells.Glial tumors seem to be able to create a favorable environment for the invasion of glioma cells in cerebral parenchyma when they combine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The expression of VEGF has been frequently associated with the grade of meningiomas and with their different histological types, but, to date, the information gathered to support this hypothesis appears to be conflicting. VEGF acts as a major vascular permeability factor and as a mitogen/survival promoter for endothelial cells and plays a key role in the formation of peritumoral edema [ 64 ]. Yamasaki et al demonstrated that high levels of VEGF expression were significantly associated with tumor recurrence, suggesting that this factor is one of the main predictors of recurrence [ 65 ].…”
Section: Genetic and Biomarkers For Meningiomasmentioning
confidence: 99%
“…The expression of VEGF has been frequently associated with the grade of meningiomas and with their different histological types, but, to date, the information gathered to support this hypothesis appears to be conflicting. VEGF acts as a major vascular permeability factor and as a mitogen/survival promoter for endothelial cells and plays a key role in the formation of peritumoral edema [ 64 ]. Yamasaki et al demonstrated that high levels of VEGF expression were significantly associated with tumor recurrence, suggesting that this factor is one of the main predictors of recurrence [ 65 ].…”
Section: Genetic and Biomarkers For Meningiomasmentioning
confidence: 99%